1995
DOI: 10.1177/030089169508100503
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, Alcohol, Diet and Risk of prostate Cancer

Abstract: A hospital-based case-control study of the association between tobacco smoking, alcohol drinking and several relevant dietary items and prostate cancer was carried out in the National Cancer Institute of Uruguay between January 1988 and December 1994. The sample included 156 patients with histologically proven prostatic cancer and 302 controls with a variety of neoplastic and non-neoplastic diseases. The results showed increased risks of prostate cancer associated with beer drinking, meat, milk and fruit consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 21 publications
1
33
1
Order By: Relevance
“…29). For nine evaluated case-control studies (202)(203)(204)(206)(207)(208)(209)(210)(211), the mean relative risk for high versus low consumption was 0.90 and the range was 0.6-1.39 (Fig. 30).…”
Section: Prostatementioning
confidence: 99%
“…29). For nine evaluated case-control studies (202)(203)(204)(206)(207)(208)(209)(210)(211), the mean relative risk for high versus low consumption was 0.90 and the range was 0.6-1.39 (Fig. 30).…”
Section: Prostatementioning
confidence: 99%
“…In many case-control studies, men consuming relatively high levels of milk and other dairy products are at an either statistically significant increased risk (1)(2)(3)(4)(5)(6)(7) or suggestively increased risk of prostate cancer (8)(9)(10)(11) compared with low or nonconsumers, although several studies have not supported an association (12,13). A recent meta-analysis of 11 casecontrol studies that met the specified inclusion criteria found a combined odds ratio (OR) of 1.68 [95% confidence interval (95% CI), 1.34-2.12] for prostate cancer comparing the highest with the lowest quantile of consumption of milk (14).…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study (De Stefani et al, 1994), the mortality rate for prostate cancer has increased by 77% in the period between 1953 and 1991. Also, migrants from Spain and Italy have increased their risk of prostate cancer after arrival in Uruguay, suggesting the importance of environmental factors (De Stefani et al, 1990).In the only previous analytic study conducted in Uruguay (De Stefani et al, 1995), diet was assessed by food groups; both red meat and dairy foods were associated with an increased risk of prostate cancer. Also, fruit intake was associated with a risk increase of 70% (De Stefani et al, 1995).…”
mentioning
confidence: 99%
“…In the only previous analytic study conducted in Uruguay (De Stefani et al, 1995), diet was assessed by food groups; both red meat and dairy foods were associated with an increased risk of prostate cancer. Also, fruit intake was associated with a risk increase of 70% (De Stefani et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation